#### Answer

$-2x^{3}$

#### Work Step by Step

$\sqrt[5]-32 x^{15}= -2x^{3}$
because,
$(-2x^{3})^5=-32x^{15}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$-2x^{3}$

$\sqrt[5]-32 x^{15}= -2x^{3}$
because,
$(-2x^{3})^5=-32x^{15}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.